Potential preventive effects of proactive therapy on sensitization in moderate to severe childhood atopic dermatitis: A randomized, investigator‐blinded, controlled study - Tatsuki Fukuie; Satoshi Hirakawa; Masami Narita; Ichiro Nomura; Kenji Matsumoto; Y. Tokura; Yukihiro Ohya (2016)
Abstract Proactive therapy for atopic dermatitis ( AD ) effectively prevents exacerbation. However, its role in preventing subsequent sensitization to allergens has not been prospectively studied. We investigated whether proactive therapy for AD can effectively impact immunological parameters in a randomized, investigator‐blinded, parallel group study. Thirty patients aged 3 months to 7 years with moderate to severe AD who had undergone an AD educational program were allocated to a proactive treatment group or a reactive treatment group. During the disease control period, patients in the proactive group performed intermittent preventive application of topical corticosteroid for 1 year. Changes in the severity scoring, quality of life measures and immunological parameters (serum thymus and activation regulated chemokine [ TARC ], total immunoglobulin E [IgE] and house dust mite‐specific IgE levels) were evaluated and compared between the proactive and reactive treatment groups. Although the average topical corticosteroid ointment use per day in both groups was not significantly different, the severity and quality of life scores were significantly lower in the proactive group than in the reactive group at the final visit. In addition, compared with baseline levels, serum TARC levels remained significantly lower during proactive therapy, while house dust mite‐specific IgE levels were significantly increased only in the reactive group. The results suggest that in addition to controlling the severity of AD , intermittent preventive administration of topical corticosteroids may prevent an increase in aeroallergen‐specific IgE levels in patients with childhood AD . The use of TARC levels as a biomarker for AD remission is also supported.